The microbiome exists in the neuroretina and choroid in normal conditions and responds rapidly to retinal injury - Cui, Xuexue; Qi, Jinyan; Yi, Caijiao; Liu, Jian; Yuan, Xiang-Ling; Deng, Wen; Xu, Heping (Frontiers in Ophthalmology, 2025)
PurposeTo investigate the microbial profiles in the retina and RPE/choroid, and how they respond to retinal injury.MethodsAdult C57BL/6J mice were subjected to retinal laser burns using a photocoagulator. One and 24h later, the retina and RPE/choroid were collected under strict sterile conditions and processed for 16S rRNA paired-end sequencing (2×250). The data were analyzed using R software, GraphPad Prism, OmicShare, and Wekemo Bioincloud.ResultsMicrobiota were detected in the retina and RPE/choroid under normal physiological conditions. The alpha diversity was higher in the retina than in the RPE/choroid. All retinal microbiotas at the phylum level and 12 out of 14 at the genus level were shared with those of RPE/choroid. The top phyla were Firmicutes, Proteobacteria, and Actinobacteria. Retinal laser injury reduced the alpha diversity but did not affect beta diversity. In the RPE/choroid, the abundance of Actinomyces and Roseburia decreased, and the abundance of Lactobacillus increased significantly after laser injury. The abundance of Sphingomonas in the retina decreased, and the abundance of Faecalibacterium and Bifidobacterium increased (P<0.05) after laser injury in the retina. Faecalibacterium and Bifidobacterium are positively linked to Th17/IL-17 signaling and RIG-I-like receptor signaling pathways, as well as antigen processing and presentation.ConclusionsThe neuroretina and RPE/choroid have diverse microbiomes under normal conditions. Their richness and evenness are relatively stable in the retina compared to those in the RPE/choroid. Retinal laser injury enriches Faecalibacterium and Bifidobacterium in ocular tissues, and these microbiotas may participate in retinal wound healing through modulating inflammation.